Interview with Marion Fourcade: «Durkheim and Science Studies for Economic Sociology» (interviewed by Olessia Kirtchik, translated by Tatiana Filippova) - Marion Fourcade (Journal of Economic Sociology, 2013)
Marion Fourcade, Professor of Sociology at Berkley California University and the Institute of Political Studies (Sciences Po), was interviewed by Olessia Kirtchik, Senior Lecturer at National Research University Higher School of Economics (HSE), during the conference “Embeddedness and Beyond: Do Sociological Theories meet Economic Realities?” in Moscow (October, 25–28, 2012), where Fourcade presented her research entitled “The Economy as Morality Play” as a plenary speaker.In her interview, Fourcade addresses such topics as comparative methods in sociology, performativity of economic knowledge, and social production of classification. The Professor’s arguments are based on comparative research on environmental evaluation, books digitization and wine classification in France and the United States. The discussed research is aimed at comparing classification processes in these three areas (nature, wine classification and books digitization) and revealing the points of their intersection. Analyzing the recent cases of oil spill near Alaska and France, Fourcade comes to the conclusion that the performativity of knowledge is a social product itself, and it does not allow people to reconstruct the social world on their own way. Reflecting on the issue of classifications, the professor raises a question: how digitized books are catalogued on the Internet in the U.S. and France? Fourcade also shows that logics of book classification in the two countries were not identical because of differences in their relation to the hierarchy of knowledge, in digitization policy priorities and in political culture. Based on the ideas of Durkheim and Bourdieu, Fourcade argues that there is no universal method of hierarchy production in any society, and what is called “conflict of classifications” results from variety of social positions and differences between them. Fourcade wound up her interview talking about reasons why economic sociology should pay attention to categories and classifications. In her opinion, they produce not only significant economic impacts, but also reflect a special way of understanding and arranging the world in order, penetrating market structures.